2019
DOI: 10.3390/cancers11030316
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Neovascularization and Developments in Therapeutics

Abstract: Tumors undergo fast neovascularization to support the rapid proliferation of cancer cells. Vasculature in tumors, unlike that in wound healing, is immature and affects the tumor microenvironment, resulting in hypoxia, acidosis, glucose starvation, immune cell infiltration, and decreased activity, all of which promote cancer progression, metastasis, and drug resistance. This innate defect of tumor vasculature can however represent a useful therapeutic target. Angiogenesis inhibitors targeting tumor vascular end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 127 publications
0
73
0
1
Order By: Relevance
“…Therapeutic approaches that target the TME are important for the prevention of recurrence and metastasis 27 . The veterinary literature increasingly has recognized the importance of various aspects of the TME, including angiogenic activity, intratumoral hypoxia, and tumor‐infiltrating Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches that target the TME are important for the prevention of recurrence and metastasis 27 . The veterinary literature increasingly has recognized the importance of various aspects of the TME, including angiogenic activity, intratumoral hypoxia, and tumor‐infiltrating Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…For tumors with very small volume (1-2 mm 3 ), the supply of oxygen and nutrients from neighboring capillaries via vascular cooption 16 is sufficient because the diffusion distance of oxygen is 100-200 mm. 19 To grow beyond this size, generation of new blood vessels toward the tumor, i.e., neovascularization, is required. 9,15 Mathivet et al 23 observed a progres- in an orthotopic mouse model.…”
Section: Early Gb Recurrence Detection With Vammentioning
confidence: 99%
“…Thus suggesting that oncogene-induced senescence represents a genuine protective physiological process [53]. On the contrary, the tendency of the tumor group expressing high levels of B-raf V600E towards neovascularization is indicative of rapid cancer cell proliferation, tumor invasion and cancer progression in general [54].…”
Section: Discussionmentioning
confidence: 99%